Evaluación del ruido ambiental generado por fuentes móviles en el casco urbano de la ciudad de machachi cantón mejía, provincia de pichincha, periodo 2015-2016 - Llanos Canchig, Víctor Paul (2016)
The noise is generated by mobile and stationary sources and its importance as a pollutant agent dates from ancient times and its involvement was conceived only as aural discomfort. The development of research on the subject has found that prolonged exposure to noise results in the gradual loss of the character of those exposed, physiological damage that alter the functioning of the heart rate, breathing and psyche. The latter one has to do with stress, moodiness, irritability, between others....